Effect of Serum on the Yield of Lymphocytic Choriomeningitis Virus in Baby Hamster Kidney Cells - Stanwick, Trevor L. (1971)
The yields of the Armstrong and WE strains of lymphocytic choriomeningitis virus in baby hamster kidney (BHK) cells cultivated in either bovine, calf, fetal bovine, or horse serum were investigated. Lines of BHK cells were established in these sera. When the infected cell lines were observed by immunofluorescence, the per cent fluorescing cells for a given virus strain did not vary. However, for both strains, the extracellular virus yields per cell were significantly greater in the fetal bovine-cell line than in the other serum-cell lines.